Changing Languages, Cultures,and Self: The Adult ESL Experience of Perspective Transformation - Kathleen P. King (Adult Education Research Conference, 1999)
Research was conducted among 208 adult ESL learners enrolled in college-based ESL programs. This study reveals that perspective transformation is frequently experienced in this context, and characterizes its nature. Implications for adult learning theory, education practice, and further research are discussed.